2019
DOI: 10.1111/epi.16371
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic inherited SCN8A variants, a rare cause of SCN8A‐related developmental and epileptic encephalopathy

Abstract: Objective: Monoallelic de novo gain-of-function variants in the voltage-gated sodium channel SCN8A are one of the recurrent causes of severe developmental and epileptic encephalopathy (DEE). In addition, a small number of de novo or inherited monoallelic loss-of-function variants have been found in patients with intellectual disability, autism spectrum disorder, or movement disorders. Inherited monoallelic variants causing either gain or loss-of-function are also associated with less severe conditions such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…18 In the pediatric cohort, PPRT2 and KCNQ2 are among the most common genetic findings, whereas we did not see these genes at all in our cohort. Additionally, we found just a single patient with a variant in SCN8A, 19 and none with variants in SCN2A, even though these genes are some of the most common genetic causes of epilepsy 7 (Johannesen et al, manuscript in preparation). The same characteristics are found in a recent study by Borlot et al, where they found one patient with an SCN2A variant, one patient with a pathogenic variant in KCNQ2 (who had been seizure-free for several years, illustrating a stable epilepsy), and none with SCN8A.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…18 In the pediatric cohort, PPRT2 and KCNQ2 are among the most common genetic findings, whereas we did not see these genes at all in our cohort. Additionally, we found just a single patient with a variant in SCN8A, 19 and none with variants in SCN2A, even though these genes are some of the most common genetic causes of epilepsy 7 (Johannesen et al, manuscript in preparation). The same characteristics are found in a recent study by Borlot et al, where they found one patient with an SCN2A variant, one patient with a pathogenic variant in KCNQ2 (who had been seizure-free for several years, illustrating a stable epilepsy), and none with SCN8A.…”
Section: Discussionmentioning
confidence: 80%
“…However, reports on adults harboring these variants are extremely limited. 19 The genes causing self-limiting epilepsy, such as PPRT2, will not be seen at our center at all. Furthermore, the TSC1 and TSC2 genes are not seen in our cohort, primarily because these patients have been diagnosed in childhood (as tuberous sclerosis is a relatively recognizable diagnosis) and are not referred for genetic testing as adults.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one variants were deleterious, either frameshift, stop or splice-site variants. Three patients had biallelic missense variants 34 . Sixty-one recurring missense variants were found in 244 affected individuals.…”
Section: Genetic Landscape Of Scn8a Variantsmentioning
confidence: 99%
“…Consequently, electrophysiological changes such as increased current density, shifting steady-state activation, and inactivation to negative and positive values, respectively, enhanced persistent current, accelerated recovery from inactivation, and delayed fast inactivation can cause gain-of-function (GoF) in the channel. Also, decreased current density, positive shift in steady-state activation, negative shift in steady-state inactivation, and slower recovery from inactivation can cause loss-of-function (LoF) ( Mantegazza et al., 2005 ; Liao et al., 2010 ; Lossin et al., 2012 ; Catterall, 2014b ; Vanoye et al., 2014 ; Wagnon et al., 2017 ; Yang et al., 2018 ; Zaman et al., 2018 ; Wengert et al., 2019 ; Zhang S. et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%